Impact of Epstein–Barr virus infection in patients with inflammatory bowel disease - Zhang, Hui; Zhao, Shuliang; Cao, Zhijun (Frontiers in Immunology, 2022)
A high prevalence of Epstein–Barr virus (EBV) infection in patients with inflammatory bowel disease (IBD) has been reported in many case reports and studies; thus, the association between EBV and IBD has gained increasing attention. Patients with IBD are at an increased risk of opportunistic EBV infection owing to the common use of immunomodulators. EBV infection in IBD patients can cause various complications, including superimposed viral colitis, which is associated with chronicity, exacerbation, and poor prognosis of refractory IBD, and can induce progression to lymphoproliferative disorders, such as EBV-positive mucocutaneous ulcer (EBVMCU), lymphomatoid granulomatosis (LYG), hemophagocytic lymphohistiocytosis (HLH) and diffuse large B-cell lymphoma (DLBCL). It has been suggested to screen for EBV before initiating immunosuppressive therapy and monitor the status of EBV infection in patients with IBD, especially those who are EBV-seronegative and have a risk of primary EBV infection. Clinicians should also be careful of misdiagnosing IBD and EBV-associated lymphoproliferative diseases due to similarities in both clinical symptoms and endoscopic manifestations. Withdrawal of immunosuppressants has been shown to be an effective strategy to achieve remission of disease at the time of EBV diagnosis, but antiviral therapy remains controversial. The present review aims to describe the characteristics of the complications caused by EBV infection and generalize the recent research progress on and challenges caused by EBV infection in IBD patients.